Measles Antibody Titres In 0-5 Years Children At Aligarh - Kandpal S D; Malik A; Khan Z (Wolters Kluwer Medknow Publications, 1999)
Research Question: What is the level of measles antibodies in 0-5 year children? Objectives: 1.To assess the pattern of decline of maternal antibodies in 0-9 months infants. 2. To estimate the seropositivity for measles antibodies in vaccinated 9 months infants. Study design: Cross- sectional. Setting: Rural areas of District Aligarh, U.P. Participants: 456 children in the age group of 0-5 years. Statistical analysis: Percentages, correlation coefficient. Results: 1. In all the study subjects below 9 months of age, the transplacentally acquired maternal measles antibodies showed a linear decline with increase in age. Out of 202 study subjects who had been immunized against measles 195(96.50%) were seropositive and 7(3.5%) were seronegative for measles antibodies.